Navigating exceptionalism: the role of public libraries in times of crisis and war rhetoric - Carlsson, Hanna; Engström, Lisa (Information research, 2025)
Introduction. This article presents the first results from the LibPrepare research project, which explores how the democratic mission of public libraries is understood, imagined and potentially compromised in times of crisis and war rhetoric. The aim is to gain knowledge of the mechanisms, motives and potential implications of enrolling libraries in Swedish national security policy. Method. A thematic text analysis is conducted of three sets of policy texts from national government, national library and professional development sources, reviewing libraries’ roles and obligations in times of crisis and war rhetoric. Analysis. The concepts of new public governance, governmentality and exceptionalism are used to explore how public library actors articulate their role in the emerging politics of emergency preparedness. Results. The library sector in Sweden is not identified as a prominent or leading actor in crisis preparedness by the Swedish civil contingencies agency. However, key library actors argue that libraries should be included in and take responsibility for societal crises and war preparedness. Conclusions. The analysis shows how key library actors argue that libraries could, and presumably therefore should, take responsibility for preparing the Swedish population for crises and war. Thereby, they argue for libraries to self-govern and actively be part of the civil defence in a perceived state of exceptionalism. Such acts of responsibilisation may strengthen the legitimacy of libraries in relation to government and governing agencies. However, if libraries become megaphones for public information and promoters of information control, these acts may prove to work in the opposite direction with regard to library users.